The Global Spread of Asbestos - Arthur L. Frank; T.K. Joshi (Ubiquity Press, 2014)
Background: Asbestos continues to be used in large quantities around the world and to be an important commodity in global trade. Objective: To assess and quantify current global patterns of asbestos production, export and use; to examine global patterns of asbestos-related disease; and to examine barriers to an asbestos ban. Method: Review of the biomedical literature describing patterns of asbestos exposure and disease; review of documents from national governments, UN agencies, and NGOs on asbestos production and use. Findings: Despite widespread knowledge of the hazards of asbestos and bans on any use of asbestos in more than 50 countries, an estimated 2 million tons of asbestos continue to be used around the world each year. Although this amount is significantly less than peak annual consumption of nearly 5 million tons two decades ago, significant amounts of asbestos are still used in India, China, Russia, and some developing countries. This use of asbestos is responsible for disease today and will cause still more asbestos-related disease in the years ahead. Real and artificially manufactured controversies regarding asbestos such as arguments about the relative hazards of different asbestos fiber types and fiber sizes have impeded bans on asbestos. Conclusions: All forms of asbestos pose grave dangers to human health. All are proven human carcinogens. There is no continued justification for the use of asbestos. Its production and use should be banned worldwide.